Severity of Pain According to Visual Analog Scale in Adhesive Capsulitis of Shoulder in Diabetic Patients - Hosain, Mohammad; Rahman, Sohely; Alam, Md Mahfuzul; Islam, SM Mazharul; Islam, Khaza Amirul; Rahman, Md Mubdiur; Bhuiyan, Mohammad Kamruzzaman (Bangladesh Medical Journal, 2022)
The aim of the present study was to assess the severity of pain according to visual analog scale in adhesive capsulitis patients with DM. A descriptive, cross sectional study was conducted from January to June 2019 among 200 patients attending at Physical Medicine and Rehabilitation Department, Bangabandhu Sheikh Mujib Medical University after obtaining requisite consent from the patients. Data were collected through the assessment of patients in the Outpatient Department. The collected data were analyzed by using SPSS (version 20.1) to assess the severity of pain according to visual analog scale in adhesive capsulitis patients. The study was approved by the institutional ethical committee of BSMMU. Mean age of patients with adhesive capsulitis was 54.85±9.35 years among them more than one third (35%) was 51-55 years of age group. Among the patients 61% was female and 39% was male. Among the patients 54(27%) had adhesive capsulitis, and 146(73%) did not have. Nearly two third female patients (65%) suffered from adhesive capsulitis of shoulder than male patients (35%). The hight number of adhesive capsulitis patients suffering from moderate type of pain and visual analogue score is 4-6, where one third of them suffer from severe type (VAS score 7-10). Overall frequency of adhesive capsulitis of the shoulder among diabetic individuals attending in physical medicine and rehabilitation department of a tertiary care hospital was 27%. Most of the adhesive capsulitis patients suffering from moderate type of pain which visual analogue score is 4-6. Bangladesh Med J. 2021 May; 50(2) : 32-34